Structure and slow release property of chlorpyrifos/graphene oxide-ZnAl-layered double hydroxide composite - Liu, Jiexiang; Zhao, Qiao; Zhang, Xiaoguang (Applied clay science, 2017)
A series of the graphene oxide-ZnAl-layered double hydroxide composites loaded with pesticide chlorpyrifos (CPF/GO-LDH) were fabricated by an exfoliation-restacking method. CPF/GO-LDH composites were characterized by powder X-ray diffraction (XRD), fourier transform infrared spectroscopy (FT-IR), scanning electron microscope (SEM) and transmission electron microscopy (TEM), thermogravimetry analysis and differential scanning calorimetry (TGA-DSC). The interlayer distances of CPF/GO-LDH with various GO/LDH mass ratios were in the range of 0.70–0.87nm, which were analyzed on the basis of electrostatic interaction between LDH nanosheets and GO substrate. The combustion temperature of CPF in the composites was enhanced 130–170°C. Release behaviors of CPF/GO-LDH composites in buffer solutions were investigated and analyzed. The sustainable slow releases were observed during the whole stage studied, and the release rates and equilibrium release amounts of CPF were closely dependent on release mediums and GO/LDH mass ratios. The release behaviors of CPF/GO-LDH were fitted with pseudo second-order and parabolic diffusion models. The present study suggested that the CPF/GO-LDH could be potentially applied for controlled-release of the pesticide. •CPF/GO-LDH is well fabricated by an exfoliation-restacking method.•The interlayer distances are discussed on the basis of electrostatic interaction.•The composite displays a sustained slow release.•CPF/GO-LDH could be potentially applied for controlled-release of the pesticide.